Addition of electron acceptors stimulates methanogenesis from lipids by anaerobic sludge - Guedes, Ana P. (2013)
Incubation of anaerobic sludge with triolein or oleate in the presence of nitrate or sulphate led to an increased methane production, relatively to incubations without inorganic electron acceptor. Faster methane production was obtained in assays amended with nitrate. Methanogenesis occurred after the reduction of alternative electron acceptors.